A Data Warehouse Based Modelling Technique for Stock Market Analysis - Mondal, Debomita; Maji, Giridhar; Goto, Takaaki; C. Debnath, Narayan; Sen, Soumya (International Journal of Engineering and Technology, 2018)
The objective of this paper is identifying a warehouse model to build an analytical framework and analyze different important parameters which directly impact the changes of share market. We identify parameters that represent different viewing windows and perspectives towards stock market performance and movement trends. We categorize and define many intrinsic as well as external factors that may affect stock market as a whole. Sensex and Nifty are used as the pulse of Indian stock market. In this paper, we focus on defining a suitable OLAP model which can cater all the parameters that affect share market. We also identify different applications of this analytical model for forecasting information to help decision making.Â Â